Influence of Dispersal Asymmetry on Total Biomass in Two-Patch Environment with Generalized Growth Rate - Bilel Elbetch (Journal of Optimization, Differential Equations and Their Applications)
In this paper, we consider a two-patch model coupled by migration terms, where each patch follows a generalized logistic law. In the first consideration, we assume that the two patches are sources and in the second, we assume that one patch is source and the second is sink. Two complete classifications for two models (source-source and source-sink) are given: one concerning when dispersal asymmetry causes smaller or larger total biomass than no dispersal, and the other addressing how the total biomass changes with dispersal asymmetry. For two models, we find that the total biomass is either strictly decreasing or initially strictly increasing then strictly decreasing with respect to dispersal asymmetry. Populations are persist in both patches for source-source case and going to extinction in both patches for source-sink case.